A review of regulatory enforcement, corporate governance and market reactions - Kwan, Jing-Hui; Lau, Wee-Yeap (2011)
The past decades witnessed the massive growth of literature on corporate governance. Various perspectives of corporate governance mechanisms were widely documented. However, studies on corporate governance from the regulatory perspective receive relatively little attention. Majority review papers focus largely on internal and external corporate governance mechanism literatures. This paper intends to give an overview on the literatures on the second generation of corporate governance research as suggested by Denis and McConnell. Literatures on legal and regulatory mechanism are reviewed. In addition, this paper highlighted the roles and importance of regulatory investor protection, regulatory enforcement and compliance behavior. The consequences of corporate misconduct and stock market reactions followed by identification of research gap and suggestions for future research are discussed.